Kosovodrömmar . My Promised Land - Söderqvist, Jonas; Sjödin, Oskar (Marionettfilm, 2008)
Verzio FF Submission In Kosovo, Dafi and Teuta are planning their wedding. Tetua works in an American army kitchen in Iraq and Dafi takes on various jobs, trying to make ends meet. In the vacuum left behind after the US-led invasion, unemployment is sky high and almost all parts of civil structure have crumbled. Life in Kosovo offers few or no possibilities to create a safe haven for a young family. But Dafi and Teuta struggle, having decided to make the best of their lives. The only career opportunities in Kosovo are those with the UNMIK organization, the KFOR-forces or with some of the multitude of American army contractors supplying the US army bases with stores, restaurants and supply work. So what happens when the armies move on to the next conflict? How do you build a future and start a family in a country torn by war? A film about hope and despair in Europe.